The Immunomodulatory Potential of Ethanolic Extract of Blue Butterfly Pea Flower (Clitoria ternatea) on Non-Specific Immune Mechanisms - Ermalyanti Fiskia; Muhammad Azhar A Karim; Muhammad Fakhrur Rajih Hi Yusuf; Rufaidah Azzahra; Ismail Rahman (Jurnal FARMASIMED (JFM), 2026)
The immune system is a complex mechanism consisting of cells, tissues, and organs that work in coordination to protect the body from exposure to pathogens. However, pathogens also possess strategies to counteract immune defenses, thereby necessitating external substances to support immune enhancement. One such substance is antioxidants. Butterfly pea flower (Clitoria ternatea) is a potential candidate as an immunomodulator due to its high antioxidant content, which functions to prevent lipid peroxidation and combat free radicals. This study aims to investigate the immunomodulatory potential of the ethanol extract of butterfly pea flower using the carbon clearance test in mice. The research method was experimental, employing 30 BALB/c mice as test animals, which were divided into six groups: Butterfly Pea Flower Extract (EBTB) at doses of 150, 300, and 600 mg/kg BW, levamisole 25 mg and methylprednisolone 4 mg as comparison groups, and sodium CMC as the negative control group. The substances were administered orally for seven consecutive days, followed by intravenous induction of carbon ink on day 8. The obtained serum was measured for absorbance using UV-Vis spectrophotometry at 650 nm. Parameters observed included the phagocytic index (PI) and lymphoid organ index (liver, spleen, and thymus). Based on the phagocytic index calculation, EBTB at doses of 150 and 300 mg/kg BW yielded values of 2.990 and 2.929, respectively, indicating strong immunostimulant activity, while BPFE at 600 mg/kg BW showed moderate immunostimulant activity with a PI value of 1.423. Results for the lymphoid organ index in the BPFE 150 group did not show significant differences (P > 0.05) compared to the control group. In conclusion, the ethanol extract of butterfly pea flower demonstrates potential as an immunomodulator for nonspecific immune responses.